(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The role and the place at the system of preparation of the future social teachers in a higher educational institution reveals in the article; the position of that the system of the organization of educational activity of the future social teachers should consider innovations which take place at stages of development and formation of school of thought of social pedagogics is proved.